Carbon nanotube dispersion liquid, and electrode coating material, electrode, and non-aqueous electrolyte secondary battery using same

By combining carboxymethyl cellulose with specific etherification and molecular weight in the carbon nanotube dispersion liquid with a specific etherification degree and molecular weight with a single layer of carbon nanotube, the problem of unstable dispersion in water is solved, and high concentration dispersion and excellent battery performance are achieved.

CN119790473APending Publication Date: 2025-04-08DKS CO LTD

Patent Information

Application Number
CN202380062614.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-30
Filing Date
2023-08-29
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art is difficult to disperse the single layer of carbon nanotubes in water at a high concentration and stably, resulting in poor battery performance in the electrode coating of nonaqueous electrolyte secondary batteries.

Method used

The carbon nanotube dispersion liquid formed by combining carboxymethylcellulose with an etherification degree of 0.65 to 0.85 and a weight average molecular weight of 120,000 to 250,000 to 250,000 to 250,000 to carbon nanotubes, has a content of 0.47 to 1.00 mass % to improve dispersion stability and battery performance.

Benefits of technology

A high concentration of dispersion liquid containing single-layer carbon nanotubes is achieved, with excellent dispersion stability and significantly improved battery performance in the electrode coating of nonaqueous electrolyte secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005289357610000231
    Figure BDA0005289357610000231
  • Figure BDA0005289357610000241
    Figure BDA0005289357610000241
Patent Text Reader

Abstract

Provided is a carbon nanotube dispersion liquid having excellent dispersion stability of single-layer carbon nanotubes. A carbon nanotube dispersion liquid according to an embodiment contains single-layer carbon nanotubes, carboxymethyl cellulose and / or a salt thereof, and water, wherein the content of the single-layer carbon nanotubes is 0.47-1.00 mass%. The carboxymethyl cellulose and / or the salt thereof contains at least one type of carboxymethyl cellulose and / or a salt thereof having a degree of etherification of 0.65-0.85 and a weight-average molecular weight of 120,000-250,000. The content of the carboxymethyl cellulose and / or the salt thereof is 120-220 parts by mass per 100 parts by mass of the single-layer carbon nanotubes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present invention relate to a carbon nanotube dispersion, and an electrode coating, an electrode, and a nonaqueous electrolyte secondary battery using the carbon nanotube dispersion. Background Art

[0002] Carbon nanotubes have excellent electrical conductivity and are therefore used as a conductive agent constituting electrodes in non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries. However, carbon nanotubes are difficult to disperse uniformly in water because of their strong aggregation due to van der Waals forces.

[0003] In order to improve the dispersibility of carbon nanotubes in water, it is known to use carboxymethyl cellulose and / or its salt as a dispersant. For example, Patent Document 1 discloses a carbon nanotube dispersion, wherein carboxymethyl cellulose and / or its salt is used with a weight average molecular weight of 10,000 to 100,000 and an etherification degree of 0.5 to 0.9, and the product of the complex elastic modulus (Pa) and the phase angle (°) is 100 or more and 1500 or less.

[0004] Patent Document 2 discloses a carbon nanotube dispersion in which carboxymethyl cellulose and / or its salt having an etherification degree of 0.5 to 1.2 and a 1% aqueous solution viscosity of 1 to 1000 mPa·s is used.

[0005] Patent Document 3 discloses a carbon nanotube dispersion using carboxymethyl cellulose having a 3% aqueous solution viscosity of 2 to 200 mPa·s and dispersing carbon nanotubes to have a D10 of 0.3 to 1.0 μm, a D50 of 3 to 10 μm, and a D90 of 60 μm or less.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent No. 6860740

[0009] Patent Document 2: International Publication No. 2022 / 070810

[0010] Patent Document 3: International Publication No. 2022 / 137977 Summary of the invention

[0011] Technical problem that the invention aims to solve

[0012] However, among carbon nanotubes, single-walled carbon nanotubes generally have a small fiber diameter and are difficult to disperse stably in water at a high concentration. Therefore, the actual situation is that the concentration of the dispersion of single-walled carbon nanotubes circulating on the market is less than 0.4% by mass. In the above-mentioned patent documents 1 to 3, in the dispersion using only single-walled carbon nanotubes as carbon nanotubes, specifically, the embodiments only disclose a dispersion with a maximum of 0.4% by mass. Therefore, a carbon nanotube dispersion containing single-walled carbon nanotubes at a higher concentration and having excellent dispersion stability is required. In addition, when the carbon nanotube dispersion is used as, for example, an electrode coating for a non-aqueous electrolyte secondary battery, it is preferably excellent in battery performance.

[0013] An object of an embodiment of the present invention is to provide a carbon nanotube dispersion liquid which contains single-walled carbon nanotubes at a high concentration and has excellent dispersion stability, and which can obtain excellent battery performance when used as an electrode coating material for a non-aqueous electrolyte secondary battery.

[0014] Technical solutions to the problem

[0015] The present invention includes the following embodiments.

[0016] [1] A carbon nanotube dispersion comprising: single-walled carbon nanotubes, carboxymethyl cellulose and / or a salt thereof, and water, wherein the content of the single-walled carbon nanotubes is 0.47% by mass to 1.00% by mass, and the carboxymethyl cellulose and / or a salt thereof comprises at least one carboxymethyl cellulose and / or a salt thereof having an etherification degree of 0.65 to 0.85 and a weight average molecular weight of 120,000 to 250,000, and the content of the carboxymethyl cellulose and / or a salt thereof is 120 to 220 parts by mass relative to 100 parts by mass of the single-walled carbon nanotubes.

[0017] [2] A coating material for an electrode of a non-aqueous electrolyte secondary battery, comprising: the carbon nanotube dispersion described in [1]; and a silicon-based active material.

[0018] [3] An electrode for a non-aqueous electrolyte secondary battery, produced using the electrode coating material described in [2].

[0019] [4] A non-aqueous electrolyte secondary battery comprising the electrode for a non-aqueous electrolyte secondary battery according to [3].

[0020] Effects of the Invention

[0021] According to an embodiment of the present invention, it is possible to provide a carbon nanotube dispersion liquid which contains single-walled carbon nanotubes at a high concentration and has excellent dispersion stability and which can provide excellent battery performance when used as an electrode coating material for a non-aqueous electrolyte secondary battery. DETAILED DESCRIPTION

[0022] The carbon nanotube dispersion liquid of the present embodiment contains: (A) single-walled carbon nanotubes, (B) carboxymethyl cellulose and / or a salt thereof, and (C) water.

[0023] [(A) Single-walled carbon nanotube]

[0024] Single-walled carbon nanotubes are carbon nanotubes (hereinafter sometimes referred to as CNTs), which are formed by rolling a six-membered ring network (graphene sheet) composed of carbon into a cylindrical shape. They have a single-layer structure and are also called single-walled carbon nanotubes (hereinafter sometimes referred to as SWCNTs).

[0025] Carbon nanotubes include: single-layer carbon nanotubes (SWCNT) with a single-layer structure and multi-layer carbon nanotubes (MWCNT: multi-walled carbon nanotubes) with a multi-layer structure. Compared with multi-layer carbon nanotubes, single-layer carbon nanotubes are more flexible. Therefore, when used as a conductive agent for an electrode, the battery performance (cycle characteristics) is excellent. In detail, when a silicon-based active material such as SiO is used as an active material for an electrode, the volume change caused by the expansion and contraction of the electrode during charging and discharging of the battery is large. Single-layer carbon nanotubes are softer than multi-layer carbon nanotubes, so they can follow the above-mentioned volume change and can improve the cycle characteristics of the battery.

[0026] The diameter (fiber diameter) of a single-walled carbon nanotube is not particularly limited, and the average diameter may be, for example, 0.4 to 100 nm, 0.5 to 10 nm, or 1.0 to 5.0 nm. The length of a single-walled carbon nanotube is not particularly limited, and the average length may be, for example, 50 nm to 1 mm, or 0.5 to 100 μm. The aspect ratio (i.e., the ratio of the average length to the average diameter) of a single-walled carbon nanotube is not particularly limited, and may be, for example, greater than 10, or greater than 100.

[0027] Here, the average diameter and average length of single-walled carbon nanotubes can be obtained by measuring the dimensions of 50 single-walled carbon nanotubes randomly selected from the atomic force microscope image and taking the arithmetic mean. For the mm-level length that cannot be measured by atomic force microscope, it can be measured using the image based on the microscope.

[0028] In the carbon nanotube dispersion of the present embodiment, the carbon nanotubes are basically single-walled carbon nanotubes, but multi-walled carbon nanotubes may also be included within a range that does not impair the effect. In one embodiment, the carbon nanotube dispersion preferably has a ratio of 80% by mass or more of single-walled carbon nanotubes in the total carbon nanotubes, more preferably 95% by mass or more, further preferably 98% by mass or more, and may also be 100% by mass.

[0029] [(B) carboxymethyl cellulose and / or its salt]

[0030] Carboxymethyl cellulose and / or its salt (hereinafter sometimes referred to as CMC) has a structure in which the hydroxyl groups in the glucose residues constituting cellulose are substituted with carboxymethyl ether groups. CMC may have a carboxyl group (-COOH), may have a carboxylate salt form, or may use both.

[0031] Examples of the salt of carboxymethyl cellulose include alkali metal salts such as sodium salts, lithium salts, potassium salts, alkaline earth metal salts such as calcium salts, magnesium salts, ammonium salts, alkylamine salts, alkanolamine salts and other organic salts. These salts may include only one or more salts. Among them, alkali metal salts are preferred, and sodium salts are more preferred.

[0032] The present embodiment is characterized in that at least one CMC having a degree of etherification of 0.65 to 0.85 and a weight average molecular weight (Mw) of 120,000 to 250,000 is used as CMC. By using CMC having a degree of etherification of 0.65 to 0.85 and a weight average molecular weight of 120,000 to 250,000, the dispersion stability of single-walled carbon nanotubes can be improved, and the battery performance when used as an electrode coating can be improved.

[0033] In detail, by making the degree of etherification of CMC to be 0.65 or more, the hydrophilicity can be improved to improve the dispersibility and dispersion stability of the single-walled carbon nanotubes. By making the degree of etherification of CMC to be 0.85 or less, the adhesion to the single-walled carbon nanotubes is improved. Therefore, not only at the stage of the carbon nanotube dispersion liquid, but also at the subsequent stage of the electrode coating, the aggregation of the single-walled carbon nanotubes is suppressed, and the battery performance can be improved. The degree of etherification of CMC is more preferably 0.70 to 0.80.

[0034] In this specification, the etherification degree of CMC is measured by the following method.

[0035] (Degree of etherification)

[0036] 0.6 g of CMC was dried at 105°C for 4 hours. After accurately weighing the mass of the dried product, it was wrapped with filter paper and ashed in a magnetic crucible. The ash was transferred to a 500 mL beaker, 250 mL of water and 35 mL of 0.05 mol / L aqueous sulfuric acid solution were added, and boiled for 30 minutes. After cooling, the excess acid was back-titrated with 0.1 mol / L aqueous potassium hydroxide solution (using phenolphthalein as an indicator). The degree of etherification was calculated according to the following formula.

[0037] Formula: (etherification degree) = 162 × A / (10000-80A)

[0038] A = (af-bf1) / mass of dried product (g)

[0039] A: The amount of 0.05 mol / L sulfuric acid aqueous solution consumed by the binding base in 1 g of the sample (mL)

[0040] a: Usage amount (mL) of 0.05 mol / L sulfuric acid aqueous solution

[0041] f: Titration degree (in Japanese: titer) of 0.05 mol / L sulfuric acid aqueous solution

[0042] b: Titration amount (mL) of 0.1 mol / L potassium hydroxide aqueous solution

[0043] f1: Titration degree of 0.1 mol / L potassium hydroxide aqueous solution

[0044] By making the weight-average molecular weight of CMC 250,000 or less, the viscosity of the carbon nanotube dispersion can be reduced, the single-walled carbon nanotubes can be made highly concentrated, and the dispersibility can be improved. By making the weight-average molecular weight of CMC 120,000 or more, the adhesion to single-walled carbon nanotubes is improved, and the dispersibility and dispersion stability can be improved. Specifically, if the weight-average molecular weight of CMC is less than 120,000, the molecular chain of CMC is short, and the adhesion to single-walled carbon nanotubes is reduced. That is, CMC either adheres to single-walled carbon nanotubes or separates from single-walled carbon nanotubes. Therefore, even if single-walled carbon nanotubes can be dispersed at the stage of the carbon nanotube dispersion, at the stage of the electrode coating later, CMC will separate from single-walled carbon nanotubes, and single-walled carbon nanotubes will aggregate, sometimes reducing the battery performance. In contrast, by making the weight-average molecular weight of CMC 120,000 or more, the adhesion to single-walled carbon nanotubes can be improved, the dispersion stability of the carbon nanotube dispersion can be improved, and the battery performance can be improved. The weight-average molecular weight of CMC is preferably 130,000 to 200,000, more preferably 140,000 to 180,000.

[0045] In this specification, the weight-average molecular weight of CMC is measured by GPC (Gel Permeation Chromatography). Specifically, it is measured by the following method.

[0046] (Weight-average molecular weight)

[0047] · Apparatus

[0048] High-speed HPLC: Prominence-i LC-2030, manufactured by Shimadzu Corporation Detector: Differential refractive index detector RID-20A, manufactured by Shimadzu Corporation Column: TSKgel G3000 SW + G4000SW + guard column, manufactured by Tosoh Corporation

[0049] · Measurement method

[0050] 0.08 mol / L sodium acetate aqueous solution was used as the mobile phase solvent. About 66 mg of the active ingredient was dissolved in 10 mL of the mobile phase solvent, and 10 μL was injected after filtering. The analysis conditions were as follows: flow rate [mL / min] = 0.70, column temperature = 40°C, and measurement pressure [kg / cm 2 ]=1~15, measurement time [min]=60, and polyethylene oxide with known molecular weight is used as the standard substance.

[0051] In this embodiment, as CMC, CMC (B1) having an etherification degree of 0.65 to 0.85 and a weight average molecular weight of 120,000 to 250,000 may be used together with other CMC (B2). That is, in one embodiment, the CMC of the (B) component may include: carboxymethyl cellulose and / or its salt (B1) having an etherification degree of 0.65 to 0.85 (preferably 0.70 to 0.80) and a weight average molecular weight of 120,000 to 250,000 (preferably 130,000 to 200,000, more preferably 140,000 to 180,000), and other carboxymethyl cellulose and / or its salt (B2).

[0052] Here, as CMC (B1), only one CMC having a degree of etherification and a weight average molecular weight satisfying the above ranges may be used, or two or more CMCs having a degree of etherification and a weight average molecular weight satisfying the above ranges may be used.

[0053] As CMC (B2), CMC (B2) in which at least one of the degree of etherification and the weight average molecular weight deviates from the numerical range of CMC (B1) can be used. As CMC (B2), it is preferred to use CMC in which the degree of etherification satisfies the numerical range of CMC (B1) and the weight average molecular weight does not satisfy the range of CMC (B1). As such CMC (B2), the following CMC (B2-1) and CMC (B2-2) can be mentioned, and either one of them can be used or both can be used in combination.

[0054] CMC (B2-1): carboxymethyl cellulose and / or its salt having a degree of etherification of 0.65 to 0.85 (preferably 0.70 to 0.80) and a weight average molecular weight of less than 120,000 (preferably 50,000 to 100,000)

[0055] CMC (B2-2): carboxymethyl cellulose and / or its salt having an etherification degree of 0.65 to 0.85 (preferably 0.70 to 0.80) and a weight average molecular weight exceeding 250,000 (preferably 300,000 to 1,000,000, more preferably 400,000 to 900,000)

[0056] In one embodiment, the ratio of CMC (B1) in the carbon nanotube dispersion to the total CMC is preferably 30% by mass or more, more preferably 60% by mass or more, further preferably 80% by mass or more, and may be 100% by mass. That is, the CMC as the (B) component may be composed of 30% to 100% by mass (preferably 60% to 100% by mass, more preferably 80% to 100% by mass) of CMC (B1) and 0% to 70% by mass (preferably 0% to 40% by mass, more preferably 0% to 20% by mass) of CMC (B2-1) and / or CMC (B2-2). In this case, CMC (B2-1) and / or CMC (B2-2) are arbitrary components, and therefore may be 0% by mass or may contain 5% by mass or more (preferably 10% by mass or more).

[0057] [Carbon Nanotube Dispersion Liquid]

[0058] The carbon nanotube dispersion liquid of the present embodiment contains the above-mentioned components (A) and (B), and contains water as the component (C), and is a dispersion liquid in which carbon nanotubes are dispersed in water.

[0059] Water as a dispersion medium can arbitrarily contain a water-soluble organic solvent. As a water-soluble organic solvent, for example, organic solvents mixed with water such as methanol, ethanol, propanol, butanol, methyl cellosolve, ethyl cellosolve, butyl cellosolve, acetone, N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), dimethyl sulfoxide, pyrrolidine, 2-pyrrolidone, dimethylacetamide, etc. can be cited. They can use any one, or two or more can be used in combination. In one embodiment, the carbon nanotube dispersion preferably uses only water as a dispersion medium and does not contain a water-soluble organic solvent.

[0060] In the carbon nanotube dispersion, the content of the single-layer carbon nanotubes of the component (A) (i.e., the amount of the single-layer carbon nanotubes contained in 100% by mass of the carbon nanotube dispersion) is 0.47% to 1.00% by mass. As described above, the single-layer carbon nanotubes have the advantage of being softer than the multi-layer carbon nanotubes, but on the other hand, they have poor dispersibility and dispersion stability in water. For example, if it is a multi-layer carbon nanotube, it can be stably dispersed even at a concentration of about 5% by mass, while in the past, it was difficult to stably obtain a dispersion exceeding 0.4% by mass for single-layer carbon nanotubes. According to this embodiment, by using the unique CMC of the above-mentioned component (B), a carbon nanotube dispersion having a high concentration of more than 0.47% by mass and excellent dispersibility and dispersion stability can be obtained.

[0061] The content of the single-walled carbon nanotubes in the carbon nanotube dispersion is preferably 0.57% by mass to 0.95% by mass, and more preferably 0.65% by mass to 0.90% by mass.

[0062] In the carbon nanotube dispersion, the content of CMC of component (B) is 120 to 220 parts by mass relative to 100 parts by mass of the single-walled carbon nanotubes of component (A). That is, the mass ratio of (B) / (A) is set in the range of 1.20 to 2.20. By making the mass ratio of (B) / (A) greater than 1.20, the dispersibility and dispersion stability of the single-walled carbon nanotubes can be improved, and the electrode coating and battery performance can be improved. By making the mass ratio of (B) / (A) less than 2.20, the viscosity of the carbon nanotube dispersion can be suppressed, and the electrode coating and battery performance can be improved.

[0063] The mass ratio of (B) / (A) is preferably 1.30 to 2.15, more preferably 1.40 to 1.70, and even more preferably 1.50 to 1.65.

[0064] The amount of CMC as the component (B) contained in 100% by mass of the carbon nanotube dispersion is not particularly limited, and may be, for example, 0.61% to 2.15% by mass, 0.74% to 2.04% by mass, or 0.84% ​​to 1.94% by mass.

[0065] In the carbon nanotube dispersion, the content of water as component (C) is not particularly limited and may be 50% to 98.92% by mass, 70% to 98.8% by mass, 90% to 98.7% by mass, or 95.0% to 98.5% by mass relative to 100% by mass of the carbon nanotube dispersion.

[0066] The viscosity of the carbon nanotube dispersion is not particularly limited, but is preferably less than 8 Pa·s at 25° C., more preferably less than 6 Pa·s, and even more preferably less than 4 Pa·s.

[0067] The carbon nanotube dispersion of the present embodiment may contain the water-soluble organic solvent and various other additives as required in addition to the above-mentioned components (A) to (C). Examples of additives include: conductive agents other than component (A), water-soluble polymers other than component (B), dispersants, surfactants, wetting agents, defoaming agents, pH adjusters, etc.

[0068] The method for preparing the carbon nanotube dispersion is not particularly limited. For example, the above-mentioned components (A) and (B) can be mixed with water of component (C), and dispersed using a dispersing device such as a homogenizer, a high-pressure homogenizer, and an ultrasonic homogenizer to prepare the carbon nanotube dispersion. In one embodiment, it is preferred to use a dispersing device with a circulation unit, and the mixed solution containing components (A) to (C) is circulated while being dispersed using a dispersing device such as a homogenizer.

[0069] [Electrode coating]

[0070] The carbon nanotube dispersion can be used as an electrode coating for a non-aqueous electrolyte secondary battery. An electrode coating according to one embodiment includes the carbon nanotube dispersion and a silicon-based active material.

[0071] Compared with carbon materials such as graphite, silicon-based active materials can achieve high capacity, but as mentioned above, the volume change caused by charging and discharging is large. In the case of the electrode coating of the above embodiment, single-layer carbon nanotubes with excellent flexibility are used as carbon nanotubes, so that the volume change caused by charging and discharging can be followed, and the cycle characteristics of the battery can be improved. Therefore, both high capacity and cycle characteristics can be taken into account.

[0072] Examples of silicon-based active materials include SiO x Silicon oxide (hereinafter referred to as SiO) represented by (0.5≤x≤1.6), Li 2y Si (2+y) A silicon-containing compound in which Si fine particles are dispersed in a lithium silicate phase represented by (0<y<2).

[0073] The amount of the carbon nanotube dispersion in the electrode coating is not particularly limited, and can be 0.05% to 0.5% by mass, or 0.07% to 0.2% by mass, relative to 100% by mass of the solid content of the electrode coating (non-volatile components other than the dispersion medium, the same below), as the content of the single-layer carbon nanotubes. The content of the silicon-based active material in the electrode coating is also not particularly limited, and can be 10% to 90% by mass, or 15% to 35% by mass, relative to 100% by mass of the solid content of the electrode coating.

[0074] The electrode coating contains the above-mentioned carbon nanotube dispersion and silicon-based active material, and as needed, it also contains various components such as: electrode active materials other than silicon-based active materials, conductive agents other than carbon nanotubes, binders, thickeners, dispersants, defoaming agents, leveling agents, solvents (such as water), etc.

[0075] As electrode active materials other than silicon-based active materials, known positive electrode active materials and negative electrode active materials can be used. The electrode coating of the present embodiment is preferably used to manufacture the negative electrode of a non-aqueous electrolyte secondary battery. Therefore, as an electrode active material used in combination with a silicon-based active material, various negative electrode active materials can be used, for example, graphite (carbon-based active materials) such as natural graphite, artificial graphite, difficult graphitized carbon, and easy graphitized carbon, metal materials such as metallic lithium, alloys, and tin compounds, lithium transition metal nitrides, crystalline metal oxides, amorphous metal oxides, conductive polymers, etc. can be listed. They can be used in any one manner, or in combination of two or more. The amount of the electrode active material in the electrode coating is not particularly limited, and relative to 100% by mass of the solid content of the electrode coating, the total amount with the silicon-based active material can be 80% by mass to 97% by mass, or 93% by mass to 97% by mass.

[0076] The conductive agent other than the carbon nanotubes is not particularly limited, and examples thereof include carbon blacks such as acetylene black and Ketjen black. The amount of the conductive agent in the electrode coating is not particularly limited, and may be 0.15% to 4.3% by mass, or 0.16% to 2.2% by mass, based on 100% by mass of the solid content of the electrode coating, in terms of the total amount with the single-walled carbon nanotubes.

[0077] The binder (binder resin) is not particularly limited, and examples thereof include various resin emulsions such as styrene butadiene rubber (SBR) emulsion, polyurethane emulsion, polyvinyl acetate emulsion, and acrylic resin emulsion. The amount of the binder in the electrode coating is not particularly limited, and may be 1.5% to 9.5% by mass, or 2% to 4% by mass, relative to 100% by mass of the solid content of the electrode coating.

[0078] The thickener is not particularly limited, and for example, the same CMC as the above-mentioned component (B) may be additionally added, or a CMC different from the component (B) may be separately added.

[0079] [Non-aqueous electrolyte secondary battery]

[0080] A non-aqueous electrolyte secondary battery in one embodiment includes an electrode made using the electrode coating. The electrode for the non-aqueous electrolyte secondary battery may be a positive electrode or a negative electrode, preferably a negative electrode. The non-aqueous electrolyte secondary battery is preferably a lithium ion secondary battery.

[0081] The electrode for a non-aqueous electrolyte secondary battery may include a current collector and an active material layer formed on the current collector, wherein the active material layer is formed from the electrode coating. That is, the electrode can be produced by applying the electrode coating to the current collector and drying it.

[0082] As a current collector, as long as it is an electronic conductor that does not produce adverse effects in the non-aqueous electrolyte secondary battery formed, there is no particular limitation. For example, in addition to copper, stainless steel, nickel, aluminum, titanium, sintered carbon, conductive polymer, conductive glass, Al-Cd alloy, etc., for the purpose of improving adhesion, conductivity, oxidation resistance, it is possible to use a material obtained by treating the surface of copper, etc. using carbon, nickel, titanium, silver, etc. These current collectors can be current collectors that have been oxidized on the surface. Regarding the shape of the current collector, in addition to foil, it is also possible to use a film-like, sheet-like, mesh-like, punched or expanded material, lath body, porous body, foamed body and other formed bodies.

[0083] In one embodiment, the nonaqueous electrolyte secondary battery comprises a negative electrode, a positive electrode, a separator and an electrolyte disposed between the negative electrode and the positive electrode, and the negative electrode and / or the positive electrode (preferably the negative electrode) are electrodes made using the above-mentioned electrode coating. As an embodiment, the nonaqueous electrolyte secondary battery may have: a stacked body formed by alternately stacking the negative electrode and the positive electrode across a separator, a container for accommodating the stacked body, and an electrolyte such as a nonaqueous electrolyte injected into the container. As a nonaqueous electrolyte, for example, a nonaqueous electrolyte formed by dissolving a lithium salt as a supporting electrolyte in an organic solvent can be used to form a lithium ion secondary battery.

[0084] Example

[0085] Hereinafter, the present invention will be described in more detail based on Examples and Comparative Examples, but the present invention is not limited thereto.

[0086] The details of each component used in Examples and Comparative Examples are shown below.

[0087] [(A) ingredient]

[0088] ·CNT-1: single-walled carbon nanotube (SWCNT). Purity = 96.5% by mass, average diameter = 1.6 nm, average fiber length = 5 μm. “TUBALL BATT” manufactured by OCSiAl

[0089] · CNT-2: Multi-walled carbon nanotube (MWCNT). Purity = 98% by mass, average diameter = 10 nm, average fiber length = 10 μm. “FT9000” manufactured by Cnano Corporation

[0090] [(B) ingredient]

[0091] CMC-1: carboxymethyl cellulose sodium salt. Etherification degree = 0.75, weight average molecular weight = 150,000. Synthesized according to Synthesis Example 1 below.

[0092] (Synthesis example 1)

[0093] 2020 g of solvent (isopropanol / water = 80 / 20 (mass ratio)), 579 g of 50 mass% sodium hydroxide aqueous solution and 550 g of flaky cellulose (165 g of coniferous tree N-DSP, 385 g of broadleaved tree L-DSP) were placed in a biaxial kneader type reactor, and an alkali cellulose reaction was carried out at 25° C. for 90 minutes. Next, a mixture of 330 g of monochloroacetic acid adjusted to 25° C. and 152 g of solvent (isopropanol / water = 80 / 20 (mass ratio)) was added dropwise to the obtained reaction solution over 60 minutes, and the temperature was raised to 78° C. over 25 minutes, and an etherification reaction was further carried out for 70 minutes. Next, the obtained reaction solution was cooled to 60° C., and the pH was adjusted to 8.5 using a 50 mass% acetic acid aqueous solution, and the reaction solvent was gasified and recovered using a reduced pressure filter to obtain a crude carboxymethyl cellulose sodium salt. The obtained crude carboxymethylcellulose sodium salt was washed with methanol in an amount 10 times the mass and dried at 105° C. for 45 minutes. The obtained dried product was pulverized using an impact mill (pulverizer manufactured by Hosokawa Micron Co., Ltd.) to obtain carboxymethylcellulose sodium salt (CMC-1).

[0094] CMC-2: carboxymethyl cellulose sodium salt. Etherification degree = 0.76, weight average molecular weight = 200,000. Synthesized according to Synthesis Example 2 below.

[0095] (Synthesis example 2)

[0096] 2020 g of solvent (isopropanol / water = 80 / 20 (mass ratio)), 579 g of 50% by mass sodium hydroxide aqueous solution and 550 g of flake cellulose (conifer N-DSP) were placed in a biaxial kneader type reactor and subjected to an alkali cellulose reaction at 25° C. for 120 minutes. Next, a mixture of 334 g of monochloroacetic acid and 152 g of solvent (isopropanol / water = 80 / 20 (mass ratio)) adjusted to 25° C. was added dropwise to the obtained reaction solution over 60 minutes, and the temperature was raised to 78° C. over 25 minutes, and an etherification reaction was further conducted for 70 minutes. Next, the obtained reaction solution was cooled to 60° C., and the pH was adjusted to 8.5 using a 50% by mass acetic acid aqueous solution, and the reaction solvent was gasified and recovered using a vacuum filter to obtain a crude carboxymethyl cellulose sodium salt. The obtained crude carboxymethyl cellulose sodium salt was washed with 10 times the mass of methanol and dried at 105° C. for 45 minutes. The obtained dried product was pulverized using an impact mill (pulverizer manufactured by Hosokawa Micron Co., Ltd.) to obtain carboxymethylcellulose sodium salt (CMC-2).

[0097] CMC-3: carboxymethyl cellulose sodium salt. Etherification degree = 0.74, weight average molecular weight = 120,000. Synthesized according to Synthesis Example 3 below.

[0098] (Synthesis example 3)

[0099] 2020 g of solvent (isopropanol / water = 80 / 20 (mass ratio)), 579 g of 50% sodium hydroxide aqueous solution and 550 g of flaky cellulose (broadleaf L-DSP) were put into a biaxial kneader type reactor and subjected to alkali cellulose reaction at 25°C for 90 minutes. Next, a mixture of 325 g of monochloroacetic acid and 152 g of solvent (isopropanol / water = 80 / 20 (mass ratio)) adjusted to 25°C was added dropwise to the obtained reaction solution for 60 minutes, and the temperature was raised to 78°C for 25 minutes, and an etherification reaction was further carried out for 70 minutes. Next, the obtained reaction solution was cooled to 60°C, and the pH was adjusted to 8.5 using a 50% acetic acid aqueous solution, and the reaction solvent was gasified and recovered using a vacuum filter to obtain a crude carboxymethyl cellulose sodium salt. The obtained crude carboxymethyl cellulose sodium salt was washed with 10 times the mass of methanol and dried at 105°C for 45 minutes. The obtained dried product was pulverized using an impact mill (pulverizer manufactured by Hosokawa Micron Co., Ltd.) to obtain carboxymethylcellulose sodium salt (CMC-3).

[0100] CMC-4: carboxymethyl cellulose sodium salt. Etherification degree = 0.76, weight average molecular weight = 250,000. Synthesized according to Synthesis Example 4 below.

[0101] (Synthesis Example 4)

[0102] 2020 g of solvent (isopropanol / water = 80 / 20 (mass ratio)), 579 g of 50% by mass sodium hydroxide aqueous solution and 550 g of flake cellulose (conifer N-DSP) were placed in a biaxial kneader type reactor and subjected to alkali cellulose reaction at 25° C. for 90 minutes. Next, a mixture of 334 g of monochloroacetic acid and 152 g of solvent (isopropanol / water = 80 / 20 (mass ratio)) adjusted to 25° C. was added dropwise to the obtained reaction solution over 60 minutes, and the temperature was raised to 78° C. over 25 minutes, and an etherification reaction was further conducted for 70 minutes. Next, the obtained reaction solution was cooled to 60° C., and the pH was adjusted to 8.5 using a 50% by mass acetic acid aqueous solution, and the reaction solvent was gasified and recovered using a vacuum filter to obtain a crude sodium carboxymethyl cellulose salt. The obtained crude sodium carboxymethyl cellulose salt was washed with 10 times the mass of methanol and dried at 105° C. for 45 minutes. The obtained dried product was pulverized using an impact mill (pulverizer manufactured by Hosokawa Micron Co., Ltd.) to obtain carboxymethylcellulose sodium salt (CMC-4).

[0103] CMC-5: carboxymethyl cellulose sodium salt. Etherification degree = 0.66, weight average molecular weight = 158,000. Synthesized according to Synthesis Example 5 below.

[0104] (Synthesis Example 5)

[0105] 2020 g of solvent (isopropanol / water = 80 / 20 (mass ratio)), 579 g of 50 mass% sodium hydroxide aqueous solution and 550 g of flaky cellulose (165 g of coniferous tree N-DSP, 385 g of broadleaved tree L-DSP) were placed in a biaxial kneader type reactor, and an alkali cellulose reaction was carried out at 25° C. for 90 minutes. Next, a mixture of 290 g of monochloroacetic acid adjusted to 25° C. and 152 g of solvent (isopropanol / water = 80 / 20 (mass ratio)) was added dropwise to the obtained reaction solution over 60 minutes, and the temperature was raised to 78° C. over 25 minutes, and an etherification reaction was further carried out for 70 minutes. Next, the obtained reaction solution was cooled to 60° C., and the pH was adjusted to 8.5 using a 50 mass% acetic acid aqueous solution, and the reaction solvent was gasified and recovered using a reduced pressure filter to obtain a crude carboxymethyl cellulose sodium salt. The obtained crude carboxymethylcellulose sodium salt was washed with methanol in an amount 10 times the mass, and dried at 105° C. for 45 minutes. The obtained dried product was pulverized using an impact mill (pulverizer manufactured by Hosokawa Micron Co., Ltd.) to obtain carboxymethylcellulose sodium salt (CMC-5).

[0106] CMC-6: carboxymethyl cellulose sodium salt. Etherification degree = 0.85, weight average molecular weight = 149,000. Synthesized according to Synthesis Example 6 below.

[0107] (Synthesis Example 6)

[0108] 2020 g of solvent (isopropanol / water = 80 / 20 (mass ratio)), 579 g of 50 mass% sodium hydroxide aqueous solution and 550 g of flaky cellulose (165 g of coniferous tree N-DSP, 385 g of broadleaved tree L-DSP) were placed in a biaxial kneader type reactor, and an alkali cellulose reaction was carried out at 25° C. for 90 minutes. Next, a mixture of 374 g of monochloroacetic acid adjusted to 25° C. and 152 g of solvent (isopropanol / water = 80 / 20 (mass ratio)) was added dropwise to the obtained reaction solution over 60 minutes, and the temperature was raised to 78° C. over 25 minutes, and an etherification reaction was further carried out for 70 minutes. Next, the obtained reaction solution was cooled to 60° C., and the pH was adjusted to 8.5 using a 50 mass% acetic acid aqueous solution, and the reaction solvent was gasified and recovered using a vacuum filter to obtain a crude carboxymethyl cellulose sodium salt. The obtained crude carboxymethylcellulose sodium salt was washed with methanol in an amount 10 times the mass, and dried at 105° C. for 45 minutes. The obtained dried product was pulverized using an impact mill (pulverizer manufactured by Hosokawa Micron Co., Ltd.) to obtain carboxymethylcellulose sodium salt (CMC-6).

[0109] CMC-7: carboxymethyl cellulose sodium salt. Etherification degree = 0.73, weight average molecular weight = 106,000. Synthesized according to Synthesis Example 7 below.

[0110] (Synthesis Example 7)

[0111] 2020 g of solvent (isopropanol / water = 80 / 20 (mass ratio)), 579 g of 50% by mass sodium hydroxide aqueous solution and 550 g of flaky cellulose (broadleaf L-DSP) were put into a biaxial kneader type reactor and subjected to alkali cellulose reaction at 25°C for 120 minutes. Next, a mixture of 321 g of monochloroacetic acid and 152 g of solvent (isopropanol / water = 80 / 20 (mass ratio)) adjusted to 25°C was added dropwise to the obtained reaction solution for 60 minutes, and the temperature was raised to 78°C for 25 minutes, and an etherification reaction was further conducted for 70 minutes. Next, the obtained reaction solution was cooled to 60°C, and the pH was adjusted to 8.5 using a 50% by mass acetic acid aqueous solution, and the reaction solvent was gasified and recovered using a pressure reducing filter to obtain a crude carboxymethyl cellulose sodium salt. The obtained crude carboxymethyl cellulose sodium salt was washed with 10 times the mass of methanol and dried at 105°C for 45 minutes. The obtained dried product was pulverized using an impact mill (pulverizer manufactured by Hosokawa Micron Co., Ltd.) to obtain carboxymethylcellulose sodium salt (CMC-7).

[0112] CMC-8: carboxymethyl cellulose sodium salt. Etherification degree = 0.69, weight average molecular weight = 314,000. Synthesized according to Synthesis Example 8 below.

[0113] (Synthesis Example 8)

[0114] 2020 g of solvent (isopropanol / water = 80 / 20 (mass ratio)), 579 g of 50% by mass sodium hydroxide aqueous solution and 550 g of flake cellulose (165 g of cotton linter pulp, 385 g of conifer N-DSP) were placed in a biaxial kneader type reactor, and an alkali cellulose reaction was carried out at 25° C. for 90 minutes. Next, a mixture of 303 g of monochloroacetic acid adjusted to 25° C. and 152 g of solvent (isopropanol / water = 80 / 20 (mass ratio)) was added dropwise to the obtained reaction solution over 60 minutes, and the temperature was raised to 78° C. over 25 minutes, and an etherification reaction was further carried out for 70 minutes. Next, the obtained reaction solution was cooled to 60° C., and the pH was adjusted to 8.5 using a 50% by mass acetic acid aqueous solution, and the reaction solvent was vaporized and recovered using a vacuum filter to obtain a crude carboxymethyl cellulose sodium salt. The obtained crude carboxymethyl cellulose sodium salt was washed with 10 times the mass of methanol and dried at 105° C. for 45 minutes. The obtained dried product was pulverized using an impact mill (pulverizer manufactured by Hosokawa Micron Co., Ltd.) to obtain carboxymethylcellulose sodium salt (CMC-8).

[0115] CMC-9: carboxymethyl cellulose sodium salt. Etherification degree = 0.69, weight average molecular weight = 510,000. Synthesized according to Synthesis Example 9 below.

[0116] (Synthesis Example 9)

[0117] 2020 g of solvent (isopropanol / water = 80 / 20 (mass ratio)), 579 g of 50% by mass sodium hydroxide aqueous solution and 550 g of flake cellulose (385 g of cotton linter pulp, 165 g of conifer N-DSP) were placed in a biaxial kneader type reactor, and an alkali cellulose reaction was carried out at 25° C. for 90 minutes. Next, a mixture of 303 g of monochloroacetic acid adjusted to 25° C. and 152 g of solvent (isopropanol / water = 80 / 20 (mass ratio)) was added dropwise to the obtained reaction solution over 60 minutes, and the temperature was raised to 78° C. over 25 minutes, and an etherification reaction was further carried out for 70 minutes. Next, the obtained reaction solution was cooled to 60° C., and the pH was adjusted to 8.5 using a 50% by mass acetic acid aqueous solution, and the reaction solvent was vaporized and recovered using a vacuum filter to obtain a crude carboxymethyl cellulose sodium salt. The obtained crude carboxymethyl cellulose sodium salt was washed with 10 times the mass of methanol and dried at 105° C. for 45 minutes. The obtained dried product was pulverized using an impact mill (pulverizer manufactured by Hosokawa Micron Co., Ltd.) to obtain carboxymethylcellulose sodium salt (CMC-9).

[0118] CMC-10: carboxymethyl cellulose sodium salt. Etherification degree = 0.69, weight average molecular weight = 860,000. Synthesized according to Synthesis Example 10 below.

[0119] (Synthesis Example 10)

[0120] 2020 g of solvent (isopropanol / water = 80 / 20 (mass ratio)), 579 g of 50% by mass sodium hydroxide aqueous solution and 550 g of flake cellulose (cotton linter pulp) were placed in a biaxial kneader type reactor, and an alkali cellulose reaction was carried out at 25° C. for 90 minutes. Next, a mixture of 303 g of monochloroacetic acid adjusted to 25° C. and 152 g of solvent (isopropanol / water = 80 / 20 (mass ratio)) was added dropwise to the obtained reaction solution over 60 minutes, and the temperature was raised to 78° C. over 25 minutes, and an etherification reaction was further carried out for 70 minutes. Next, the obtained reaction solution was cooled to 60° C., and the pH was adjusted to 8.5 using a 50% by mass acetic acid aqueous solution, and the reaction solvent was gasified and recovered using a vacuum filter to obtain a crude carboxymethyl cellulose sodium salt. The obtained crude carboxymethyl cellulose sodium salt was washed with 10 times the mass of methanol and dried at 105° C. for 45 minutes. The obtained dried product was pulverized using an impact mill (pulverizer manufactured by Hosokawa Micron Co., Ltd.) to obtain carboxymethylcellulose sodium salt (CMC-10).

[0121] CMC-11: carboxymethyl cellulose sodium salt. Etherification degree = 0.90, weight average molecular weight = 154,000. Synthesized according to Synthesis Example 11 below.

[0122] (Synthesis Example 11)

[0123] 2020 g of solvent (isopropanol / water = 80 / 20 (mass ratio)), 579 g of 50 mass% sodium hydroxide aqueous solution and 550 g of flaky cellulose (165 g of coniferous tree N-DSP, 385 g of broadleaved tree L-DSP) were placed in a biaxial kneader type reactor, and an alkali cellulose reaction was carried out at 25° C. for 90 minutes. Next, a mixture of 400 g of monochloroacetic acid adjusted to 25° C. and 152 g of solvent (isopropanol / water = 80 / 20 (mass ratio)) was added dropwise to the obtained reaction solution over 60 minutes, and the temperature was raised to 78° C. over 25 minutes, and an etherification reaction was further carried out for 70 minutes. Next, the obtained reaction solution was cooled to 60° C., and the pH was adjusted to 8.5 using a 50 mass% acetic acid aqueous solution, and the reaction solvent was gasified and recovered using a reduced pressure filter to obtain a crude carboxymethyl cellulose sodium salt. The obtained crude carboxymethylcellulose sodium salt was washed with methanol in an amount 10 times the mass and dried at 105° C. for 45 minutes. The obtained dried product was pulverized using an impact mill (pulverizer manufactured by Hosokawa Micron Co., Ltd.) to obtain carboxymethylcellulose sodium salt (CMC-11).

[0124] CMC-12: carboxymethyl cellulose sodium salt. Etherification degree = 0.61, weight average molecular weight: 151,000. Synthesized according to Synthesis Example 12 below.

[0125] (Synthesis Example 12)

[0126] 2020 g of solvent (isopropanol / water = 80 / 20 (mass ratio)), 579 g of 50 mass% sodium hydroxide aqueous solution and 550 g of flaky cellulose (165 g of coniferous tree N-DSP, 385 g of broadleaved tree L-DSP) were placed in a biaxial kneader type reactor, and an alkali cellulose reaction was carried out at 25° C. for 90 minutes. Next, a mixture of 268 g of monochloroacetic acid and 152 g of solvent (isopropanol / water = 80 / 20 (mass ratio)) adjusted to 25° C. was added dropwise to the obtained reaction solution over 60 minutes, and the temperature was raised to 78° C. over 25 minutes, and an etherification reaction was further carried out for 70 minutes. Next, the obtained reaction solution was cooled to 60° C., and the pH was adjusted to 8.5 using a 50 mass% acetic acid aqueous solution, and the reaction solvent was gasified and recovered using a reduced pressure filter to obtain a crude carboxymethyl cellulose sodium salt. The obtained crude carboxymethylcellulose sodium salt was washed with methanol in an amount 10 times the mass and dried at 105° C. for 45 minutes. The obtained dried product was pulverized using an impact mill (pulverizer manufactured by Hosokawa Micron Co., Ltd.) to obtain carboxymethylcellulose sodium salt (CMC-12).

[0127] [Example 1 to Example 15 and Comparative Example 1 to Comparative Examples 1 to 11]

[0128] In Example 1, 0.80 g of CNT-1 and 1.20 g of CMC-1 were measured in a 200 mL beaker, 98.0 g of water was added, and the mixture was stirred and mixed for 12 hours using a stirrer (1000 rpm). Then, a tube pump was connected to an ultrasonic homogenizer ("US-600T" manufactured by Nippon Seiki Co., Ltd., with a circulation unit), and the mixed solution was dispersed for 90 minutes at an output of 100 μA while circulating the mixed solution to obtain a carbon nanotube dispersion.

[0129] In Examples 2 to 15 and Comparative Examples 1 to 11, the types and amounts of the components were changed as shown in Tables 1 and 2, and otherwise, a carbon nanotube dispersion was obtained in the same manner as in Example 1.

[0130] In Tables 1 and 2, regarding the amount of component (A), the values ​​in parentheses are the amount of SWCNT for CNT-1 and the amount of MWCNT for CNT-2. The concentration of component (A) is the concentration of CNT contained in 100% by mass of the dispersion. (B) / (A) is the mass ratio of CMC to the amount of CNT.

[0131] The carbon nanotube dispersions of Examples 1 to 15 and Comparative Examples 1 to 11 were evaluated for dispersibility, dispersion stability, viscosity, electrode coating properties, and battery performance (cycle characteristics). Each evaluation method is as follows.

[0132] [Dispersibility]

[0133] The carbon nanotube dispersion was diluted with water to a CNT content of 0.1 mass %, and then a sample was prepared and observed using an optical microscope (magnification 35 times). 2 The size of the aggregates in the test piece was measured and the dispersibility of the carbon nanotubes was evaluated according to the following 5 levels, with 3 or more being considered acceptable.

[0134] 5: There are 2 or less agglomerates smaller than 0.6 mm, 1 or less agglomerates larger than 0.6 mm and smaller than 1 mm, and no agglomerates larger than 1 mm.

[0135] 4: There are 3 or more agglomerates smaller than 0.6 mm, 1 or less agglomerates larger than 0.6 mm and smaller than 1 mm, and no agglomerates larger than 1 mm.

[0136] 3: There are two or more agglomerates that are 0.6 mm or larger and smaller than 1 mm, and there are no agglomerates that are larger than 1 mm.

[0137] 2: There are aggregates larger than 1 mm and smaller than 2 mm, and there are no aggregates larger than 2 mm.

[0138] 1: There are aggregates larger than 2 mm.

[0139] [Dispersion stability]

[0140] The carbon nanotube dispersion was left to stand for 1 month, water was added so that the CNT content became 0.001% by mass, and the absorbance (A1) at a wavelength unique to carbon nanotubes was measured using an ultraviolet-visible spectrophotometer (manufactured by Hitachi, Ltd., model: U-3900H). Then, a centrifugal separation process was performed for 80 minutes at 5000×g (MWCNT was 500×g) and 25°C using a centrifuge (manufactured by himac, model: CF16RN). The absorbance (A2) of the supernatant after the centrifugal separation process was measured in the same way. The absorbance change rate before and after centrifugation was obtained by the following formula. As a wavelength unique to carbon nanotubes, it was set to 503nm unique to metallic carbon nanotubes. The larger the value of the absorbance change rate, the less sedimentation of the carbon nanotubes that agglomerated over time based on centrifugal separation, which means that the dispersion stability is excellent. The dispersion stability is evaluated according to the following 5 levels, and 3 or more are considered qualified.

[0141] Absorbance change rate before and after centrifugation (%) = (A2 / A1) × 100

[0142] 5: The value of the absorbance change rate is 82% or more.

[0143] 4: The value of the absorbance change rate is 78% or more and less than 82%.

[0144] 3: The value of the absorbance change rate is 74% or more and less than 78%.

[0145] 2: The value of the absorbance change rate is 70% or more and less than 74%.

[0146] 1: The value of the absorbance change rate is less than 70%.

[0147] [Viscosity]

[0148] The viscosity of the carbon nanotube dispersion was measured using a B-type viscometer ("TVB-10" manufactured by Toki Sangyo Co., Ltd.) under conditions of 25° C. and 6 rpm (3 minutes). The viscosity evaluation results were expressed in the following five levels.

[0149] 5: Less than 4Pa·s

[0150] 4: 4Pa·s or more and less than 6Pa·s

[0151] 3: 6Pa·s or more and less than 8Pa·s

[0152] 2: 8Pa·s or more and less than 10Pa·s

[0153] 1: 10Pa·s or more

[0154] [Electrode coating properties]

[0155] SiO (average particle size 4.5 μm, specific surface area 5.5 m 2 / g) and graphite (average particle size 18 μm, specific surface area 3.2 m 2 / g) 100 parts by mass (containing ratio 20 / 80), 0.2 parts by mass of carbon nanotube dispersion and 1.0 parts by mass of acetylene black as a conductive agent, 0.65 parts by mass of carboxymethyl cellulose sodium salt ("Selogen (registered trademark) BSH-6" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) 1.5% by mass aqueous solution as a thickener, 3.5 parts by mass of a sodium salt aqueous dispersion of polyurethane obtained in the following Synthesis Example P1 as a binder in terms of solid content, and ion exchange water were mixed with a planetary mixer to prepare a negative electrode slurry having a solid content of 49% (39% by mass in Comparative Example 2 alone). An electrolytic copper foil having a thickness of 10 μm was used as a current collector, and a negative electrode mixture layer consisting of the above-mentioned negative electrode slurry was formed on the electrolytic copper foil. Specifically, the negative electrode slurry was applied onto an electrolytic copper foil using a coater, and after roll pressing, it was dried under reduced pressure at 130° C., thereby obtaining a negative electrode active material with a density of 5.8 to 6.6 mg / cm 2 The surface condition at this time was observed and evaluated according to the following 5 levels, and 3 or more was regarded as acceptable.

[0156] 5: The color tone of the electrode surface is uniform, and no bumps caused by aggregates or wire drawing after the electrode is cut off can be seen.

[0157] 4: Wave stripes caused by the physical properties of the coating are visible on the electrode surface, but bumps and grooves caused by condensation and wire drawing caused by electrode scraping are not visible.

[0158] 3: The bumps and grooves caused by the condensation are found on the electrode surface, but no wire drawing is seen after the electrode is cut off.

[0159] 2: Concavities and convexities caused by condensation were found on the electrode surface, and wire drawing was also observed after the electrode was cut off

[0160] 1: Difficulty in coating

[0161] Synthesis example P1:

[0162] In a four-necked flask equipped with a stirrer, a reflux cooling tube, a thermometer, and a nitrogen blowing tube, 71.3 parts by mass of polybutadiene polyol ("PolybdR-45HT" manufactured by Idemitsu Kosan Co., Ltd., average hydroxyl value 46.5 mgKOH / g, number of active hydrogen groups 2.32), 4.2 parts by mass of dimethylol propionic acid (number of active hydrogen groups 2), 24.5 parts by mass of dicyclohexylmethane diisocyanate, and 100 parts by mass of methyl ethyl ketone were added, and reacted at 75° C. for 4 hours to obtain a methyl ethyl ketone solution of a urethane prepolymer having a free isocyanate group content of 2.5% by mass relative to the non-volatile component. The solution was cooled to 45° C., 1.25 parts by mass of sodium hydroxide was added for neutralization, and then 300 parts by mass of water was slowly added, and emulsified and dispersed using a homogenizer. Next, an aqueous solution prepared by diluting 1.6 parts by mass of ethylenediamine (number of active hydrogen groups: 2) with 100 parts by mass of water was added to carry out a chain extension reaction for 1 hour. The solvent was removed under reduced pressure and heating at 50° C. to obtain an aqueous dispersion of a sodium salt of polyurethane having a nonvolatile content of about 30% by mass.

[0163] [Battery performance (cycle characteristics)]

[0164] Preparation of positive electrode for evaluation:

[0165] A planetary mixer was used to mix 92 parts by mass of LiNiCoAl (NCA) as a positive electrode active material, 4 parts by mass of acetylene black ("Li-400" manufactured by Denka (Strain) as a conductive aid, 4 parts by mass of polyvinylidene fluoride as a binder, and 49 parts by mass of N-methyl-2-pyrrolidone as a dispersion medium to prepare a positive electrode slurry with a solid content of 69% by mass. The positive electrode slurry was coated on an aluminum foil with a thickness of 15 μm using a coating machine, dried at 130°C, and then roller pressed to obtain a positive electrode active material of 16.6 mg / cm 2 The positive electrode.

[0166] Production of lithium-ion secondary batteries:

[0167] The positive electrode obtained above and the negative electrode prepared in the electrode coating evaluation were combined, and a polyolefin-based (PE / PP / PE) separator was sandwiched between the electrodes to form a separator. The positive terminal and the negative terminal were welded on each positive and negative electrode using ultrasound. The stack was placed in an aluminum laminate packaging material, and the opening for liquid injection was retained and heat-sealed. A positive electrode with an area of ​​18 cm 2 , the negative electrode area is 19.8cm 2 Next, LiPF dissolved in a solvent of ethylene carbonate and diethyl carbonate (volume ratio of 30 / 70) was injected. 6 (1.0 mol / L) of electrolyte solution was added, and the opening was heat-sealed to obtain a battery for evaluation.

[0168] Evaluation of battery performance:

[0169] The prepared lithium-ion secondary battery was subjected to a performance test of the charge and discharge cycle characteristics at 20°C. The charge and discharge cycle characteristics were measured under the following conditions. CC (constant current) charging was performed at a current density equivalent to 0.5C until 4.2V, and then switched to CV (constant voltage) charging at 4.2V. After charging for 1.5 hours, CC discharge was performed at a current density equivalent to 0.5C until 2.7V. The cycle was repeated for 300 cycles at 20°C, and the ratio of the 1C discharge capacity after 300 cycles to the initial 1C discharge capacity was taken as the 1C charge and discharge cycle retention rate. The cycle retention rate at this time was evaluated according to the following 5 levels, and 3 or more was considered qualified.

[0170] 5: 1C charge and discharge cycle retention rate is above 95%

[0171] 4: 1C charge and discharge cycle retention rate is above 90% and less than 95%

[0172] 3: 1C charge and discharge cycle retention rate is more than 80% and less than 90%

[0173] 2: 1C charge and discharge cycle retention rate is above 70% and less than 80%

[0174] 1: 1C charge and discharge cycle retention rate is less than 70%

[0175] [Table 1]

[0176]

[0177] [Table 2]

[0178]

[0179] The results are shown in Tables 1 and 2. In Comparative Example 1, the CNT concentration was high, and the dispersibility and dispersion stability were approximately acceptable, but the viscosity was high, and the electrode coating and battery performance were poor. In Comparative Example 2, the CNT concentration was low, and the dispersion stability and battery performance were poor.

[0180] In Comparative Example 3, the mass ratio (B) / (A) of CMC to CNT is low, and the amount of CMC is small, so the dispersibility and dispersion stability are poor, and the electrode coating and battery performance are poor. In Comparative Example 4, the mass ratio (B) / (A) of CMC to CNT is high, and the amount of CMC is large, so the viscosity is high, and the electrode coating and battery performance are poor.

[0182] In Comparative Example 5, the dispersibility and dispersion stability are excellent, but the battery performance is poor. This is believed to be because the molecular weight of CMC is small, so the adhesion of CMC to CNT is reduced, and CNT aggregates at the stage of electrode coating. In Comparative Examples 6 to 8, since the molecular weight of CMC is large, there is a tendency for the dispersibility or dispersion stability to decrease, and the viscosity is high, and the electrode coating and battery performance are poor.

[0183] In Comparative Example 9, the dispersibility and battery performance were poor. This is believed to be because the etherification degree of CMC was high, so the adhesion of CMC to CNT decreased, and the effect as a dispersant decreased. In Comparative Example 10, the etherification degree of CMC was low, and the dispersion stability and battery performance were poor.

[0184] Comparative Example 11 is an example using multiwalled carbon nanotubes. Although the dispersibility and the like were excellent, the electrode could not follow the volume change during charge and discharge, resulting in poor cycle characteristics.

[0185] In contrast, the carbon nanotube dispersions of Examples 1 to 15 contained single-walled carbon nanotubes at high concentrations, had excellent dispersibility and dispersion stability, had low viscosity, and were excellent in electrode coating properties and battery performance, and significant improvement effects were confirmed.

[0186] It should be noted that the various numerical ranges described in the specification can be arbitrarily combined with their upper and lower limits, and all of their combinations are recorded in this specification as preferred numerical ranges. In addition, the numerical range described as "X to Y" means greater than X and less than Y.

[0187] Several embodiments of the present invention are described above, but these embodiments are given as examples only and are not intended to limit the scope of the invention. These embodiments can be implemented in various other ways, and various omissions, substitutions, and changes can be made without departing from the scope of the subject matter of the invention. These embodiments and their omissions, substitutions, and changes are included in the scope and subject matter of the invention, and are also included in the invention described in the claims and their equivalents.

Claims

1. A carbon nanotube dispersion, characterized in that: The carbon nanotube dispersion comprises: single-walled carbon nanotubes, carboxymethyl cellulose and / or a salt thereof, and water. The content of the single-walled carbon nanotubes is 0.47 mass % to 1.00 mass %, The carboxymethyl cellulose and / or its salt comprises at least one carboxymethyl cellulose and / or its salt having a degree of etherification of 0.65 to 0.85 and a weight average molecular weight of 120,000 to 250,000. The content of the carboxymethyl cellulose and / or its salt is 120 to 220 parts by mass relative to 100 parts by mass of the single-walled carbon nanotubes.

2. A coating for electrodes of a non-aqueous electrolyte secondary battery, characterized in that: The method comprises the carbon nanotube dispersion according to claim 1 and a silicon-based active material.

3. An electrode for a non-aqueous electrolyte secondary battery, characterized in that: The electrode coating is made using the electrode coating according to claim 2.

4. A non-aqueous electrolyte secondary battery, characterized in that: A non-aqueous electrolyte secondary battery electrode according to claim 3.

Citation Information

Patent Citations

  • Dispersion fluid, electrode composition for non-aqueous electrolyte secondary battery, electrode for non-aqueous electrolyte secondary battery, non-aqueous electrolyte secondary battery, and method for producing electrode for non-aqueous electrolyte secondary battery

    WO2022070810A1

  • Electrode slurry carbon nanotube liquid dispersion, negative electrode slurry, non-aqueous electrolyte secondary battery, and method for producing electrode slurry carbon nanotube liquid dispersion

    WO2022137977A1

Cited By

  • Carbon nanotube reinforced polyacrylic adhesive, its preparation method and application

    CN122706276A